2009
DOI: 10.4049/jimmunol.182.3.1247
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity in Dry Eye Is Due to Resistance of Th17 to Treg Suppression

Abstract: Dry eye disease (DED), an inflammatory autoimmune disorder affecting the ocular surface, degrades visual performance and the quality of life of >10 million people in the United States alone. The primary limitation in the effective treatment of DED is an incomplete understanding of its specific cellular and molecular pathogenic elements. Using a validated mouse model of DED, herein we functionally characterize the different T cell subsets, including regulatory T cells (Tregs) and pathogenic effector T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
287
4
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 269 publications
(301 citation statements)
references
References 29 publications
7
287
4
3
Order By: Relevance
“…To determine whether IL-17 plays a role in the pathogenesis of experimental T. congolense infection, we treated infected C57BL/6 mice with anti-IL-17 antibody to neutralize IL-17 activity and monitored the parasitemia levels. The dose and regimen of antibody treatment used here has been shown to effectively neutralize IL-17 activity in vivo in different experimental models (4,8,31). Surprisingly, anti-IL-17 antibody-treated mice had higher peak parasitemia throughout the infection period.…”
Section: Resultsmentioning
confidence: 90%
“…To determine whether IL-17 plays a role in the pathogenesis of experimental T. congolense infection, we treated infected C57BL/6 mice with anti-IL-17 antibody to neutralize IL-17 activity and monitored the parasitemia levels. The dose and regimen of antibody treatment used here has been shown to effectively neutralize IL-17 activity in vivo in different experimental models (4,8,31). Surprisingly, anti-IL-17 antibody-treated mice had higher peak parasitemia throughout the infection period.…”
Section: Resultsmentioning
confidence: 90%
“…25 Additional studies in experimental murine dry eye have reported an IL-17A-mediated dysfunction of regulatory T cells, with a reduction of Th-17 cell expansion and restoration of Treg function after in vivo blockade of IL-17A. 43 An additional Th-17-associated cytokine, IL-21, was found to have increased mRNA expression in CD25KO compared with wild-type LG, with a significant time-related decrease. An emerging role for IL-21 in autoimmunity is supported by observations of elevated levels of the cytokine and its receptor in the sera of patients with SS, rheumatoid arthritis, systemic sclerosis, and inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 98%
“…In this context, it is of note that the recent studies suggest that autoreactive memory CD4 1 T lymphocytes induced during acute uveitis can mediate a chronic form of the disease [29]. It is also important to note that autoimmunity in Dry Eye Disease has recently been shown to due to the resistance of Th17 to Treg suppression [30]. Although the exact mechanism underlying Treg-mediated suppression of CD4 1 effector T cells is unknown, it is thought to derive in part from the prodigious consumption of IL-2 by Treg cells, resulting in the depletion of IL-2 required for expansion of CD4 1 CD25 À effector T cells.…”
Section: Discussionmentioning
confidence: 99%